Polystyrene-Poly(methyl methacrylate) Silver Nanocomposites: Significant Modification of the Thermal and Electrical Properties by Microwave Irradiation - Alsharaeh, Edreese H. (Materials (Basel), 2016)
This work compares the preparation of nanocomposites of polystyrene (PS), poly(methyl methacrylate) (PMMA), and PSMMA co-polymer containing silver nanoparticles (AgNPs) using in situ bulk polymerization with and without microwave irradiation (MWI). The AgNPs prepared were embedded within the polymer matrix. A modification in the thermal stability of the PS/Ag, PMMA/Ag, and PSMMA/Ag nanocomposites using MWI and in situ was observed compared with that of neat PSMMA, PS, and PMMA. In particular, PS/Ag, and PSMMA/Ag nanocomposites used in situ showed better thermal stability than MWI, while PMMA/Ag nanocomposites showed improved thermal stability. The electrical conductivity of the PS/Ag, PMMA/Ag, and PSMMA/Ag composites prepared by MWI revealed a percolation behavior when 20% AgNPs were used as a filler, and the conductivity of the nanocomposites increased to 103 S/cm, 33 S/cm, and 40 mS/cm, respectively. This enhancement might be due to the good dispersion of the AgNPs within the polymer matrix, which increased the interfacial interaction between the polymer and AgNPs. The polymer/Ag nanocomposites developed with tunable thermal and electrical properties could be used as conductive materials for electronic device applications.